Culturing the desert microbiota - Selmani, Zakia; Attard, Eleonore; Lauga, Béatrice; Barakat, Mohamed; Ortet, Philippe; Tulumello, Joris; Achouak, Wafa; Kaci, Yahia; Heulin, Thierry (Frontiers in Microbiology, 2023)
Over the last 30 years, the description of microbial diversity has been mainly based on culture-independent approaches (metabarcoding, metagenomics) allowing an in-depth analysis of microbial diversity that no other approach allows. Bearing in mind that these approaches should not entirely replace culture-independent approaches, we have improved an original method for isolating strains consisting of "culturating" grains of sand directly on Petri dishes (grain-by-grain method). This method allowed to cultivate up to 10% of the bacteria counted on the surface of grains of the three sites studied in the Great Western Erg in Algeria (Timoudi, Béni Abbès, Taghit), knowing that on average about 10 bacteria colonize each grain. The diversity of culturable bacteria (collection of 290 strains) identified by 16S rRNA sequencing revealed that Arthrobacter subterraneus, Arthrobacter tecti, Pseudarthrobacter phenanthrenivorans, Pseudarthrobacter psychrotolerans and Massilia agri are the dominant species. The comparison of the culture-dependent and -independent approaches at the Timoudi site revealed 18 bacterial genera common to both approaches with a relative overestimation of the genera Arthrobacter/Pseudarthrobacter and Kocuria, and a relative underestimation of the genera Blastococcus and Domibacillus by the bacterial culturing approach. The bacterial isolates will allow further study on the mechanisms of tolerance to desiccation, especially in Proteobacteria.